Rancang Bangun Demodulator FM - Ronie, Hilmun Syah; Anhar, Anhar; Amri, Rahyul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
FM demodulator is used to demodulate signal in FM receiver. Demodulation process is performed to recover the information signal. The information signal is 3.4 kHz which ismodulated with a carrier signal of 19 kHz. FM demodulator is designed with PLL (Phase Locked Loop) method, it used the concept of phase locking signal. FM demodulator withPLL method consist of four blocks, that is phase comparator, second-order Butterworth LPF, VCO wienbridge, and buffer amplifiers. Design of FM demodulator trainer begins with calculate to determine the component value which suitable with cut off frequency. The next process to make the layout of the pcb board, dissolution layout, pcb board drilling, mounting the female connectors to pcb board, installation of component connectors to the header, and make a box to place trainer FM demodulator. The results obtained at each signal FM demodulator block is different. Demodulated signal is obtained at the buffer amplifier block, where the signal is same as the output signal at function generator is 3.4 kHz.Keywords : FM Demodulator, Demodulated Signal, Phase Look Loop, Carrier Signal, Information Signal.